Analisis Game Online PUBG terhadap Problem Hasil Belajar Siswa - Jutawan, Gede; Sudarsana, I Ketut (Universitas Nusantara PGRI Kediri, 2024)
PUBG is a game that can be played together/alone by inviting friends or randomly through the friend list feature to survive in the playing arena. The team that survives until the end is considered the winner in this game and gets points called chicken dinner. This study aims to analyze the PUBG online game on the problem of learning outcomes of class XII MIPA I students at SMA Negeri 1 Busungbiu School. This study uses a qualitative research method, with the determination of informants using purposive sampling techniques. The data analysis used is data presentation, data reduction & drawing conclusions. The results of the study showed that the use of PUBG online games in most students did not combine time well, students tend to play PUBG online games rather than studying and doing homework first. This has an impact on the student learning process, where seen from the frequency of students who tend to be addicted to PUBG online games, it greatly affects the student learning process. In learning, students are less focused and engrossed in their own world rather than listening to the material presented by the teacher. Disruption of student concentration in learning affects the absorption of learning materials. This results in a lack of maximum student understanding of a material.